2021
DOI: 10.1162/netn_a_00181
|View full text |Cite
|
Sign up to set email alerts
|

Atypical core-periphery brain dynamics in autism

Abstract: The intrinsic function of the human brain is dynamic, giving rise to numerous behavioral subtypes that fluctuate distinctively at multiple timescales. One of the key dynamical processes that takes place in the brain is the interaction between core-periphery brain regions, which undergoes constant fluctuations associated with developmental time frames. Core-periphery dynamical changes associated with macroscale brain network dynamics span multiple timescales and may lead to atypical behavior and clinical sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 119 publications
(480 reference statements)
2
8
0
Order By: Relevance
“…The alteration of modular connectivity contributed by dmPFC, Pcun, IPL, and lPFC nodes was also associated with ADOS scores. These results further reinforce the critical role exhibited by the DMN and CEN nodes contributing to atypical modular organization and development of core and peripheral brain network functional organization in ASD during early development (Roy & Uddin, 2021; Uddin et al, 2013, 2015).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The alteration of modular connectivity contributed by dmPFC, Pcun, IPL, and lPFC nodes was also associated with ADOS scores. These results further reinforce the critical role exhibited by the DMN and CEN nodes contributing to atypical modular organization and development of core and peripheral brain network functional organization in ASD during early development (Roy & Uddin, 2021; Uddin et al, 2013, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…Most notable community membership and nodal discrepancies were contributed by primary visual and speech centers of the brain including areas Lateral Occipital Cortex (LoCc), Fusiform Gyrus (FG), precentral gyrus (PrG), postcentral gyrus (PoG), superior temporal gyrus (STG). The discrepancy in intermodular relationship with core brain areas such as dorso‐medial prefrontal cortex (dmPFC), precuneus (Pcun), inferior parietal lobule (IPL), and lateral prefrontal cortex (lPFC) suggests the greater the manifestation of social symptom severity the higher the discrepancy in the inter and intramodular organization and reduced global cohesiveness (Hilger et al, 2017; Keown et al, 2017; Roy & Uddin, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also suggest that dFC of neurocognitive networks in children displays age-related increases in temporal variability of FC among neurocognitive networks. These findings lay the groundwork for understanding how variation in the developing functional network dynamics is related to risk for neurodevelopmental disorders 15,52,[54][55][56] . To compare results with the dynamic fluctuations in the functional brain networks during development we quantified temporal matrices for all 12 and 6 ROIs anchored in ToM and Pain functional brain networks.…”
Section: Aging Introduces Temporal Variability In the Evolution Of Dy...mentioning
confidence: 81%
“…Patterns of regional hypo-connectivity in ASD have been widely reported (Moseley et al, 2015; Roy and Uddin, 2021;Cheng et al, 2015; Anderson et al, 2011; Nomi and Uddin,2015). Accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of these neurons is thought to lead to disinhibition of the deep cerebellar nuclei and of the uvula/nodulus lobules (Cerliani et al, 2015;Belmonte et al, 2004), which could explain the observed increased cerebellar integration and con-sequent abnormal eyes movement control in ASD patients (Trimarco et al, 2021). Patterns of regional hypo-connectivity in ASD have been widely reported (Moseley et al, 2015;Roy and Uddin, 2021;Cheng et al, 2015;Anderson et al, 2011;Nomi and Uddin, 2015). Accordingly.…”
Section: A) B) C)mentioning
confidence: 99%